Frequent inaccuracies in ABCD(2) scoring in non-stroke specialists' referrals to a daily Rapid Access Stroke Prevention service. - O'Neill, Desmond; Coughlan, Tara; Mc Cabe, Dominick; Kennelly, Sean; Collins, Daniel; Bradley, David (My University, 2013)
Abstract The ‘accuracy’ of age, blood pressure, clinical features, duration and diabetes (ABCD2) scoring by non-stroke specialists referring patients to a daily Rapid Access Stroke Prevention (RASP) service is unclear, as is the accuracy of ABCD2 scoring by trainee residents. In this prospective study, referrals were classified as ‘confirmed TIAs’ if the stroke specialist confirmed a clinical diagnosis of possible, probable or definite TIA, and ‘non-TIAs’ if patients had a TIA mimic or completed stroke. ABCD2 scores from referring physicians were compared with scores by experienced stroke specialists and neurology/geriatric medicine residents at a daily RASP clinic; inter-observer agreement was examined. Data from 101 referrals were analysed (mean age = 60.0 years, 58% male). The median interval between referral and clinic assessment was 1 day. Of 101 referrals, 52 (52%) were ‘non-TIAs’: 45 (86%) of 52 were ‘TIA mimics’ and 7 (14%) of 52 were completed strokes. There was only ‘fair’ agreement in total ABCD2 scoring between referring physicians and stroke specialists (κ = 0.37). Agreement was ‘excellent’ between residents and stroke specialists (κ = 0.91). Twenty of 29 patients scored as ‘moderate to high risk’ (score 4–6) by stroke specialists were scored ‘low risk’ (score 0–3) by referring physicians. ABCD2 scoring by referring doctors is frequently inaccurate, with a tendency to underestimate stroke risk. These findings emphasise the importance of urgent specialist assessment of suspected TIA patients, and that ABCD2 scores by non-stroke specialists cannot be relied upon in isolation to risk-stratify patients. Inter-observer agreement in ABCD2 scoring was ‘excellent’ between residents and stroke specialists, indicating short-term training may improve accuracy.
PUBLISHED
Keywords: Inter-observer agreement; Risk stratification; Prevention; ABCD2; Stroke; TIA; Ageing; Neuroscience